Attachment and Negative Relational Maintenance: Dyadic Comparisons Using an Actor-Partner Interdependence Model. Issue 5 (20th October 2017) - Goodboy, Alan K.; Dainton, Marianne; Borzea, Dana; Goldman, Zachary W.
Abstract : This study used attachment theory to examine romantic partners' use of negative behaviors to maintain their relationships. Romantic couples ( N = 227 dyads) completed self-reports of their attachment styles and use of negative relational maintenance behaviors. Actor-partner interdependence models provided dyadic results: (a) having a secure attachment produced inverse actor effects for all negative maintenance behaviors except avoidance, and inverse partner effects for allowing control and infidelity; (b) having a preoccupied or a fearful attachment produced positive actor effects for all negative maintenance behaviors and positive partner effects for allowing control; and (c) having a dismissive attachment produced positive actor effects for jealousy induction, avoidance, infidelity, and destructive conflict, and positive partner effects for jealousy induction, spying, and allowing control.